Derivatives of two-dimensional iron-phosphomolybdate nanosheets and preparation methods thereof

The derivatives of two-dimensional iron-phosphoroblastad nanosheets prepared through self-assembly technology are used as zinc-air battery catalysts, solving the problems of high cost and great environmental impact of precious metal catalysts, and achieving low cost, high activity and excellent Electrocatalytic properties.

CN119330355BActive Publication Date: 2025-02-21SHENZHEN BAOAN DONGJIANG ENVIRONMENTAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411886125.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-02-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The precious metal-based catalysts used in existing zinc-air batteries have limited their wide application due to high costs, scarce resources and attenuation of activity, and traditional synthesis pathways have a great impact on the environment.

Method used

Derivatives of two-dimensional iron-phosphomolybdate nanosheets were prepared by self-assembly technology, and the derivatives of porous two-dimensional iron-phosphomolybdate nanosheets were synthesized using the in-situ polymerization and carbonization process of dopamine for zinc Catalyst in air batteries.

Benefits of technology

It achieves low cost, high activity, excellent electrocatalytic performance and energy conversion efficiency, replaces traditional precious metal catalysts, and is simple, controllable and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330355B_ABST
    Figure CN119330355B_ABST
Patent Text Reader

Abstract

The present invention relates to a derivative of a two-dimensional iron-phosphomolybdate nanosheet and a preparation method thereof. The preparation method comprises the following steps: adding a ferric nitrate solution to a phosphomolybdic acid solution, centrifuging and washing with distilled water to obtain a two-dimensional iron-phosphomolybdate; dispersing the two-dimensional iron-phosphomolybdate in a buffer solution, subsequently adding a dopamine monomer, centrifuging and washing with distilled water, and freeze-drying to obtain a first composite material; transferring the first composite material to a covered porcelain boat, and pyrolyzing under inert atmosphere conditions to obtain a derivative of a two-dimensional iron-phosphomolybdate nanosheet. The preparation method of the derivative of the two-dimensional iron-phosphomolybdate nanosheet of the present invention is simple, controllable and environmentally friendly. The derivative of the two-dimensional iron-phosphomolybdate nanosheet of the present invention is used for high catalytic activity of oxygen reduction reaction, including a catalyst used in a zinc-air battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a novel oxidizing catalyst material, and in particular to a derivative of an iron-phosphomolybdate nanosheet prepared by a self-assembly technique and a method for preparing the same. The present invention also relates to the field of electrochemical energy storage, such as a zinc-air battery, and in particular to a catalyst used in the field of electrochemical energy storage, such as a catalyst used in a zinc-air battery, and in particular to a derivative of a two-dimensional iron-phosphomolybdate nanosheet used in a zinc-air battery and a method for preparing the same. Background Art

[0002] Faced with the worsening global energy crisis, the demand for new renewable energy storage and conversion technologies is becoming increasingly urgent. Among them, zinc-air batteries, as a renewable energy technology, play a key role. However, the currently used precious metal-based catalysts, such as those based on platinum (Pt), iridium (Ir) or ruthenium (Ru), are limited in their widespread application due to problems such as high cost, scarce resources and / or activity decay.

[0003] Therefore, it is particularly important to research and develop low-cost, highly active non-precious metal catalysts. These alternative catalysts should not only have excellent electrocatalytic performance, but also reduce environmental impact through green synthesis routes. The development of such catalysts will help reduce production costs, improve energy conversion efficiency, and promote the commercialization of zinc-air battery technology. Summary of the invention

[0004] The technical problem to be solved by the present invention is to avoid the shortcomings of the above-mentioned prior art and propose a derivative of a two-dimensional iron-phosphomolybdate nanosheet and a preparation method thereof, which has the advantages of simple method, controllability and environmental protection; the derivative of the two-dimensional iron-phosphomolybdate nanosheet of the present invention has high catalytic activity for oxygen reduction reaction, including catalysts used in zinc-air batteries, and has the advantages of low cost, high activity, excellent electrocatalytic performance and high energy conversion efficiency.

[0005] The technical solution adopted by the present invention to solve the technical problem is:

[0006] A method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet comprises the following steps in sequence:

[0007] Step A: Add the ferric nitrate solution to the phosphomolybdic acid solution and let it stand for a while to make Fe 3+ self-assemble with phosphomolybdic acid to form nanoparticles or nanosheets, centrifuge the nanoparticles or nanosheets and wash with distilled water to obtain two-dimensional iron-phosphomolybdate;

[0008] Step B, dispersing the two-dimensional iron-phosphomolybdate in a buffer solution under ultrasonic conditions, then adding dopamine monomer, and stirring at room temperature for a period of time, observing that the color of the mixture changes from brown to black; then, the mixture is centrifuged and washed with distilled water, and then freeze-dried to obtain a first composite material, and the first composite material is marked as FePOM@PDA;

[0009] Step C: transferring the FePOM@PDA into a porcelain boat with a lid, and performing pyrolysis under inert atmosphere to obtain a derivative of a two-dimensional iron-phosphomolybdate nanosheet.

[0010] In step A, the concentration of the ferric nitrate solution is 0.01-5.7 mol / L.

[0011] In step A, the concentration of the phosphomolybdic acid solution is 0.5-30 mmol / L.

[0012] In step A, the molar ratio of the ferric nitrate solution to the phosphomolybdic acid solution is (1-50):1.

[0013] In step B, the buffer solution is a Tris buffer solution, a phosphate buffer solution, an ammonia-ammonium chloride buffer solution or a sodium carbonate-sodium bicarbonate buffer solution; the pH of the buffer solution is 7.5-11.

[0014] In step B, the molar ratio of the dopamine monomer to the ferric nitrate solution is (0.1-10):1.

[0015] In step B, the mass ratio of the buffer solution to the dopamine monomer is (50-200):1.

[0016] In step C, the pyrolysis under inert atmosphere conditions is: introducing an inert gas and calcining for a period of time at a temperature of 400° C. to 1000° C. The inert gas is a high-purity inert gas, that is, an inert gas with a purity of not less than 99.99%, and the inert gas includes argon, nitrogen or helium.

[0017] The present invention also discloses a derivative of a two-dimensional iron-phosphomolybdate nanosheet, which is obtained by the preparation method of the derivative of the two-dimensional iron-phosphomolybdate nanosheet; the derivative of the two-dimensional iron-phosphomolybdate nanosheet has high catalytic activity for oxygen reduction reaction, including a catalyst used in zinc-air batteries.

[0018] Compared with the prior art, the derivatives of the two-dimensional iron-phosphomolybdate nanosheets and the preparation method thereof of the present invention have the following beneficial effects:

[0019] The present invention uses the above two-dimensional iron-phosphomolybdate as a template, and synthesizes a composite material of a porous two-dimensional iron-phosphomolybdate nanosheet derivative through the in-situ polymerization and carbonization process of dopamine. The two-dimensional iron-phosphomolybdate nanosheet derivative exhibits excellent oxygen reduction electrochemical catalytic properties, showing great potential to replace traditional precious metal catalysts (such as commercial 20% Pt / C catalysts); after being assembled into a zinc-air battery, it has a higher power density (for example, the following embodiment 1 can reach 215 milliwatts / square centimeter, while the 20% Pt / C catalyst has only 86 milliwatts / square centimeter), highlighting its commercial application prospects in energy storage and conversion technology, and has the advantages of simple preparation method, controllable and environmentally friendly, without the need to add any surfactant or additive.

[0020] The high catalytic activity of the derivatives of the two-dimensional iron-phosphomolybdate nanosheets of the present invention can be attributed to their wrinkled two-dimensional nanosheet structure, which not only increases the specific surface area and exposes more active sites, but also increases the density of active sites due to the carbon doping effect; in addition, the ultrafine Mo2C and Mo2C2 uniformly distributed in the carbon framework 12 Fe 22 C 10 The nanoparticles further enhance the catalytic activity of the catalyst; therefore, the derivatives of the two-dimensional iron-phosphomolybdate nanosheets of the present invention have high catalytic activity for oxygen reduction reactions, including catalysts used in zinc-air batteries, and have the advantages of low cost, high activity, excellent electrocatalytic performance and high energy conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the SEM (scanning electron microscope) and TEM (transmission electron microscope) images of the first composite material FePOM@PDA;

[0022] Figure 2 is an XRD (X-ray diffraction) pattern of a derivative of the two-dimensional iron-phosphomolybdate nanosheet of the present invention;

[0023] Figure 3 is a TEM (transmission electron microscope) image of a derivative of a two-dimensional iron-phosphomolybdate nanosheet of the present invention;

[0024] Figure 4 It is a comparison diagram of the power density curves of the derivative of the two-dimensional iron-phosphomolybdate nanosheet of the present invention and the commercial Pt / C catalyst applied to zinc-air batteries;

[0025] Figure 5 The following is a table comparing the performance of the catalysts prepared by various embodiments of the present invention and commercial catalysts when applied to zinc-air batteries. DETAILED DESCRIPTION

[0026] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0027] A method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet comprises the following steps in sequence:

[0028] Step A, adding ferric nitrate solution to phosphomolybdic acid solution, and standing for a period of time, the standing period of time is 0.5 to 72 hours, so that Fe 3+ Self-assembling with phosphomolybdic acid to form nanoparticles or nanosheets, centrifuging the nanoparticles or nanosheets and washing with distilled water to obtain two-dimensional iron-phosphomolybdic acid; the concentration of the ferric nitrate solution is 0.01-5.7 mol / L (mol / L); the concentration of the phosphomolybdic acid solution is 0.5-30 mmol / L (millimol / L); the molar ratio of the ferric nitrate solution to the phosphomolybdic acid solution is (1-50):1;

[0029] Step B, dispersing the two-dimensional iron-phosphomolybdate in a buffer solution under ultrasonic conditions, then adding dopamine monomer, and stirring at room temperature for a period of time, observing that the color of the mixture changes from brown to black; then, the mixture is centrifuged and washed with distilled water, and then freeze-dried to obtain a first composite material, and the first composite material is marked as FePOM@PDA; the buffer solution is Tris buffer solution, phosphate buffer solution, ammonia-ammonium chloride buffer solution or sodium carbonate-sodium bicarbonate buffer solution; the pH of the buffer solution is 7.5-11; the molar ratio of the dopamine monomer to the ferric nitrate solution is (0.1-10):1; the mass ratio of the buffer solution to the dopamine monomer is (50-200):1; the room temperature is generally 20-30°C, and it is best to keep the room temperature at about 25°C;

[0030] Step C: Transfer the FePOM@PDA to a covered porcelain boat and perform pyrolysis under an inert atmosphere to obtain a second composite material, which is a derivative of the two-dimensional iron-phosphomolybdate nanosheets. 12 Fe 22 C 10 @Mo2C / C indicates that the pyrolysis under the inert atmosphere is as follows: introducing an inert gas and calcining at a temperature of 400°C to 1000°C for a period of time; the inert gas is a high-purity inert gas, that is, an inert gas with a purity of not less than 99.99%, and the inert gas includes argon, nitrogen or helium; the calcination period is 0.5 to 24 hours; and the temperature can be reached at a heating rate of 0.5 to 10°C / min to reach a temperature of 400°C to 1000°C.

[0031] The present invention adopts high-purity inert gas, which mainly has the following functions:

[0032] First, clean reaction environment: high-purity inert gas (such as argon) can provide a clean and pollution-free reaction environment. It will not produce any by-products that react with the material, which is conducive to maintaining the purity and structural integrity of the material;

[0033] Second, protect the surface of the material: high-purity inert gas can form a protective strong gas layer to prevent the material from reacting with harmful substances such as oxygen and water in the air. This helps to ensure the purity of the two-dimensional iron-phosphomolybdate nanosheet derivatives and reduce the effects of oxidation, pollution, etc. on the performance of the two-dimensional iron-phosphomolybdate nanosheet derivatives.

[0034] In contrast, using low purity inert gases may cause the following problems:

[0035] Impurity contamination: Low-purity inert gases may contain harmful substances such as oxygen and water, resulting in reduced purity of the two-dimensional iron-phosphomolybdate nanosheet derivatives.

[0036] The present invention also provides a derivative of a two-dimensional iron-phosphomolybdate nanosheet, which is obtained by the preparation method of the derivative of the two-dimensional iron-phosphomolybdate nanosheet; the derivative of the two-dimensional iron-phosphomolybdate nanosheet has high catalytic activity for oxygen reduction reaction, including a catalyst used in zinc-air batteries.

[0037] Embodiment 1

[0038] This embodiment provides a method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet, which comprises the following steps in sequence:

[0039] Step A: Add 5 ml of 0.5 mol / L (mole / L) ferric nitrate solution to 10 ml of 25 mmol / L (millimol / L) phosphomolybdic acid solution, the molar ratio of ferric nitrate solution to phosphomolybdic acid solution is 10:1, and let it stand for 24 hours to allow Fe 3+ self-assemble with phosphomolybdic acid to form nanoparticles or nanosheets, centrifuge the nanoparticles or nanosheets and wash with distilled water to obtain two-dimensional iron-phosphomolybdate, labeled as FePOM-1;

[0040] Step B, dispersing the above two-dimensional iron-phosphomolybdate in 50 ml of Tris buffer solution under ultrasonic conditions, the pH value of the Tris buffer solution is 8.5, then adding 2.5 mmol (millimolar) dopamine monomer, the molar ratio of dopamine monomer to ferric nitrate is 1:1, the mass ratio of buffer solution to dopamine monomer is 125:1, and stirring at room temperature of 25°C for 24 hours, and observing that the color of the mixture changes from brown to black; then, the mixture is centrifuged and washed with distilled water, and then freeze-dried to obtain a first composite material, and the first composite material is marked as FePOM@PDA-1;

[0041] Step C: The FePOM@PDA-1 was transferred to a covered porcelain boat and pyrolyzed at 800°C for 5 hours under argon conditions, with a heating rate of 2°C / min to reach a temperature of 800°C, to obtain a derivative of a two-dimensional iron-phosphomolybdate nanosheet, labeled as Mo 12 Fe 22 C 10 @Mo2C / C-1.

[0042] Embodiment 2

[0043] This embodiment provides a method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet, which comprises the following steps in sequence:

[0044] Step A: Add 5 ml of 0.01 mol / L (mole / L) ferric nitrate solution to 100 ml of 0.5 mmol / L (millimol / L) phosphomolybdic acid solution, the molar ratio of ferric nitrate solution to phosphomolybdic acid solution is 1:1, and let stand for 0.5 hours to allow Fe 3+ self-assemble with phosphomolybdic acid to form nanoparticles or nanosheets, centrifuge the nanoparticles or nanosheets and wash with distilled water to obtain two-dimensional iron-phosphomolybdate, labeled as FePOM-2;

[0045] Step B, dispersing the above two-dimensional iron-phosphomolybdate in 15 ml of phosphate buffer solution under ultrasonic conditions, the pH value of the phosphate buffer solution is 7.5, then adding 0.5 mmol (millimolar) dopamine monomer, the molar ratio of dopamine monomer to ferric nitrate is 10:1, the mass ratio of buffer solution to dopamine monomer is 200:1, and stirring at room temperature of 25°C for 24 hours, and observing that the color of the mixture changes from brown to black; then, the mixture is centrifuged and washed with distilled water, and then freeze-dried to obtain a first composite material, and the first composite material is marked as FePOM@PDA-2;

[0046] Step C: The FePOM@PDA-2 was transferred to a covered porcelain boat and pyrolyzed at 400°C for 24 hours under nitrogen conditions, with a heating rate of 0.5°C / min to reach a temperature of 400°C, to obtain a derivative of a two-dimensional iron-phosphomolybdate nanosheet, labeled as Mo 12 Fe 22 C 10 @Mo2C / C-2.

[0047] Embodiment 3

[0048] This embodiment provides a method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet, which comprises the following steps in sequence:

[0049] Step A: Add 5 ml of 5.7 mol / L (mol / L) ferric nitrate solution to 19 ml of 30 mmol / L (millimol / L) phosphomolybdic acid solution, the molar ratio of ferric nitrate solution to phosphomolybdic acid solution is 50:1, and let stand for 72 hours to allow Fe 3+ self-assemble with phosphomolybdic acid to form nanoparticles or nanosheets, centrifuge the nanoparticles or nanosheets and wash with distilled water to obtain two-dimensional iron-phosphomolybdate, labeled as FePOM-3;

[0050] Step B, dispersing the above two-dimensional iron-phosphomolybdate in 22 ml of sodium carbonate-sodium bicarbonate buffer solution under ultrasonic conditions, the pH value of the sodium carbonate-sodium bicarbonate buffer solution is 10.5, then adding 2.85 mmol (millimoles) of dopamine monomer, the molar ratio of dopamine monomer to ferric nitrate is 0.1:1, the mass ratio of buffer solution to dopamine monomer is 72:1, and stirring at room temperature of 25°C for 24 hours, and observing that the color of the mixture changes from brown to black; then, the mixture is centrifuged and washed with distilled water, and then freeze-dried to obtain a first composite material, and the first composite material is marked as FePOM@PDA-3;

[0051] Step C: The FePOM@PDA-3 was transferred to a covered porcelain boat and pyrolyzed at 1000°C for 0.5 h under nitrogen conditions, with a heating rate of 10°C / min to reach a temperature of 1000°C, to obtain a derivative of a two-dimensional iron-phosphomolybdate nanosheet, labeled as Mo 12 Fe 22 C 10 @Mo2C / C-3.

[0052] Embodiment 4

[0053] This embodiment provides a method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet, which comprises the following steps in sequence:

[0054] Step A: Add 5 ml of 5.7 mol / L (mol / L) ferric nitrate solution to 19 ml of 30 mmol / L (millimol / L) phosphomolybdic acid solution, the molar ratio of ferric nitrate solution to phosphomolybdic acid solution is 50:1, and let stand for 72 hours to allow Fe 3+ self-assemble with phosphomolybdic acid to form nanoparticles or nanosheets, centrifuge the nanoparticles or nanosheets and wash with distilled water to obtain two-dimensional iron-phosphomolybdate, labeled as FePOM-4;

[0055] Step B, dispersing the above two-dimensional iron-phosphomolybdate in 22 ml of ammonia-ammonia chloride buffer solution under ultrasonic conditions, the pH value of the ammonia-ammonia chloride buffer solution is 9.5, then adding 2.85 mmol (millimoles) of dopamine monomer, the molar ratio of dopamine monomer to ferric nitrate is 0.1:1, the mass ratio of the buffer solution to the dopamine monomer is 72:1, and stirring at room temperature of 25°C for 24 hours, and observing that the color of the mixture changes from brown to black; then, the mixture is centrifuged and washed with distilled water, and then freeze-dried to obtain a first composite material, and the first composite material is marked as FePOM@PDA-4;

[0056] Step C: The FePOM@PDA-4 was transferred to a covered porcelain boat and pyrolyzed at 1000°C for 0.5 hours under nitrogen conditions, with a heating rate of 10°C / min to reach a temperature of 1000°C, to obtain a derivative of a two-dimensional iron-phosphomolybdate nanosheet, labeled as Mo 12 Fe 22 C 10 @Mo2C / C-4.

[0057] The derivatives of the two-dimensional iron-phosphomolybdate nanosheets prepared in Examples 1 to 4 above were used as catalysts to prepare and test zinc-air batteries:

[0058] (1) First, 5 mg (milligram) of the derivative (catalyst) of the two-dimensional iron-phosphomolybdate nanosheet prepared in Examples 1 to 4 was dissolved in 900 μl of distilled water and 100 μl of 5% Nafion ethanol solution, respectively, and ultrasonically treated for 60 minutes to form a 5 mg / ml uniform suspension. Then, 200 μl of the suspension was uniformly coated on 1.0 cm2 of carbon fiber paper to form a 1 mg / cm2 catalyst loading layer.

[0059] (2) A 2.5 cm × 2 cm × 0.3 mm zinc foil was polished and used as the anode. In 28 ml of 6 molar KOH solution (potassium hydroxide solution), the air cathode was paired with the zinc anode to assemble a zinc-air battery.

[0060] (3) The zinc-air battery was subjected to a linear sweep voltammetry (LSV) test in the test range of 1.6 V to 0.4 V and a scan rate of 5 mV / s to obtain a power density curve of the zinc-air battery.

[0061] The derivatives of the two-dimensional iron-phosphomolybdate nanosheets prepared in the above-mentioned Examples 1 to 4 and the commercial catalysts are respectively used as catalysts in zinc-air batteries. The performance comparison table is as follows: Figure 5 shown.

[0062] from Figure 5 It can be seen from the data that the derivatives of the two-dimensional iron-phosphomolybdate nanosheets prepared in Examples 1 to 4 are respectively used as catalysts in zinc-air batteries, and the peak power is mW / cm 2 The peak power of the commercial (and commonly used in the market) 20% Pt / C catalyst (platinum content 20% platinum carbon catalyst) is 86, mW / cm 2 In academia, mW cm is also used. −2 to express; from Figure 4 It can also be seen that the power density curve of the derivative of the two-dimensional iron-phosphomolybdate nanosheet of the present invention applied to the zinc-air battery is Figure 1 It is directly above the power density curve of commercial Pt / C catalyst applied to zinc-air batteries, indicating that the derivatives of the two-dimensional iron-phosphomolybdate nanosheets prepared by the present invention are of great significance in developing cheap alternative catalysts with high activity and green synthesis routes.

[0063] Figure 1 It is the SEM (scanning electron microscope) and TEM (transmission electron microscope) images of the first composite material FePOM@PDA; Figure 1 The figure marked as a is the SEM image of the first composite material FePOM@PDA, and it can be seen that the morphology of the first composite material FePOM@PDA is wrinkled nanosheets; Figure 1 The figure marked as b is a low-magnification TEM image of the first composite material FePOM@PDA, which confirms again that the first composite material FePOM@PDA is a nanosheet morphology, and the nanosheet is porous; Figure 1 The figure marked as c is a high-magnification TEM image of the first composite material FePOM@PDA. It can be seen that the nanosheets are evenly dispersed and there are no agglomerated nanoparticles. The selected area diffraction pattern in the lower right corner shows very fuzzy and wide diffraction rings, proving that the first composite material FePOM@PDA is in an amorphous state. Figure 1 The figure marked with d is Figure 1From the high-resolution TEM image of the red box in the figure marked c, we can see that the atoms are arranged chaotically and disorderly, which once again proves that the first composite material FePOM@PDA is in an amorphous state.

[0064] Figure 2 The XRD (X-ray diffraction) diagram of the derivative of the two-dimensional iron-phosphomolybdate nanosheet of the present invention shows that the derivative of the two-dimensional iron-phosphomolybdate nanosheet (Mo 12 Fe 22 C 10 @Mo2C / C) This complex contains Mo 12 Fe 22 C 10 and Mo2C; Figure 2 The 2Ɵ below the abscissa 50 means that the X-ray diffractometer scans the entire diffraction area at an angle of 2Ɵ, which can be understood as an angle.

[0065] Figure 3 is a TEM (transmission electron microscope) image of a derivative of a two-dimensional iron-phosphomolybdate nanosheet of the present invention; Figure 3 The figure marked as a is a derivative of two-dimensional iron-phosphomolybdate nanosheets Mo 12 Fe 22 C 10 @Mo2C / C low magnification TEM morphology, indicating that the derivative Mo of the two-dimensional iron-phosphomolybdate nanosheet 12 Fe 22 C 10 @Mo2C / C is a nanosheet composed of nanoparticles embedded in a carbon matrix; Figure 3 The figure marked with b is Figure 3 The enlarged view of a region in the figure marked as a further observation of the derivative Mo of the two-dimensional iron-phosphomolybdate nanosheet 12 Fe 22 C 10 @The nanosheets of Mo2C / C are uniformly dispersed with nanoparticles of different sizes; Figure 3 The figure marked as c is a high-resolution TEM image of a derivative of a two-dimensional iron-phosphomolybdate nanosheet. Figure 3 The enlarged image of the red mark 1 in the figure marked as b. The red mark in the figure c is the (112) crystal plane of the Mo2C particle, and its interplanar spacing is 0.213 nm, proving that the very small particles are Mo2C; Figure 3 The figure marked as d is also a high-resolution TEM image of the derivative of the two-dimensional iron-phosphomolybdate nanosheet. Figure 3 The enlarged image of the red mark 2 in the figure marked as b, and the red mark Mo in the figure d 12 Fe 22 C 10The (-313) and (-113) planes of the particles have interplanar spacings of 0.209 nm and 0.199 nm, respectively, proving that the large particles are made of Mo 12 Fe 22 C 10 The upper right corner of Figure d is the Fourier transform of the orange dashed box area in Figure d. The crystal shape of the large particles is very good, and Mo can be marked. 12 Fe 22 C 10 It is monoclinic.

[0066] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, all equivalent changes and modifications made to the scope of the claims of the present invention should belong to the scope covered by the claims of the present invention.

Claims

1. A method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet, comprising the following steps in sequence: Step A: Add the ferric nitrate solution to the phosphomolybdic acid solution and let it stand for a while to make Fe 3+ self-assemble with phosphomolybdic acid to form nanoparticles or nanosheets, centrifuge the nanoparticles or nanosheets and wash with distilled water to obtain two-dimensional iron-phosphomolybdate; Step B, dispersing the two-dimensional iron-phosphomolybdate in a buffer solution under ultrasonic conditions, then adding dopamine monomer, and stirring at room temperature for a period of time, observing that the color of the mixture changes from brown to black; then, the mixture is centrifuged and washed with distilled water, and then freeze-dried to obtain a first composite material, and the first composite material is marked as FePOM@PDA; Step C: transferring the FePOM@PDA into a porcelain boat with a lid, and performing pyrolysis under inert atmosphere to obtain a derivative of a two-dimensional iron-phosphomolybdate nanosheet.

2. The method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet according to claim 1, characterized in that: In step A, the concentration of the ferric nitrate solution is 0.01-5.7 mol / L.

3. The method for preparing the derivative of the two-dimensional iron-phosphomolybdate nanosheet according to claim 1, characterized in that: In step A, the concentration of the phosphomolybdic acid solution is 0.5-30 mmol / L.

4. The method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet according to claim 1, characterized in that: In step A, the molar ratio of the ferric nitrate solution to the phosphomolybdic acid solution is (1-50):

1.

5. The method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet according to claim 1, characterized in that: In step B, the buffer solution is a Tris buffer solution, a phosphate buffer solution, an ammonia-ammonium chloride buffer solution or a sodium carbonate-sodium bicarbonate buffer solution; the pH of the buffer solution is 7.5-11.

6. The method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet according to claim 1, characterized in that: In step B, the molar ratio of the dopamine monomer to the ferric nitrate solution is (0.1-10):

1.

7. The method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet according to claim 1, characterized in that: In step B, the mass ratio of the buffer solution to the dopamine monomer is (50-200):

1.

8. The method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet according to claim 1, characterized in that: In step C, the pyrolysis is carried out under inert atmosphere conditions by introducing inert gas and calcining at a temperature of 400° C. to 1000° C. for a period of time.

9. The method for preparing a derivative of a two-dimensional iron-phosphomolybdate nanosheet according to claim 8, characterized in that: The inert gas is a high-purity inert gas, that is, an inert gas with a purity of not less than 99.99%, and the inert gas includes argon, nitrogen or helium.

10. A derivative of a two-dimensional iron-phosphomolybdate nanosheet, characterized in that: A two-dimensional iron-phosphomolybdate nanosheet derivative obtained by the preparation method of a two-dimensional iron-phosphomolybdate nanosheet derivative according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Mo2C and carbon-coated molybdenum-based heterostructure material as well as preparation method and application thereof

    CN114538517A

  • Noble metal single atom or cluster-porous molybdenum carbide / carbon nanocomposite using dynamic arrangement of noble metal atoms, method for manufacturing same, catalyst for hydrogen evolution reaction or hydrogen oxidation reaction comprising same, and electrode comprising the catalyst

    US20230378481A1